DAMPAK PERUSAHAAN KELAPA SAWIT (Elaeis guineesis Jacq.) TERHADAP PENGEMBANGAN USAHATANI DI DESA MAKMUR JAYA KECAMATAN KONGBENG KABUPATEN KUTAI TIMUR (The Impact of Palm Oil (Elaeis guineesis Jacq.) Company to the Development of Farming in Makmur Jaya Village Kongbeng Subregency East Kutai Regency) - MUHAMMAD ZAKI; TETTY WIJAYANTI (Universitas Mulawarman (University of Mulawarman), 2019)
Palm oil plantation has developed rapidly in East Kutai Regency. This study aimed to know farming diversity before and after the establishment of palm oil company in Makmur Jaya Village, Kongbeng Subregency, East Kutai Regency and the impact of palm oil company establishment. The method used in this study was purposive sampling with total samples of 30 respondents. Method of data analysis was t test. The result of study showed that the diversity of farming before the establishment of palm oil company in Makmur Jaya Village such as farming of paddy, hybrid coconut, corn, and cacao. The diversity of farming after the establishment of palm oil company in Makmur Jaya Village are farming of palm oil, paddy, and pepper. Palm oil company has given the very significant impact to the development of farming in Makmur Jaya Village from the result of t test as many as 5.18.